2013
DOI: 10.1111/ijd.12109
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and laboratory features of chronic idiopathic urticaria in the elderly

Abstract: CIU in the elderly population is nearly equally distributed in both sexes and is characterized by fewer wheals, lower rates of concomitant symptomatic dermographism, lower rates of angioedema, and lower ASST positivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 21 publications
2
48
1
Order By: Relevance
“…In our study, we found a lack of female predominance in the elderly CU group, despite a 57.9% proportion of females in the total study population. This finding is in concordance with a previous report of an almost equal sex distribution in an elderly CU group [17]. All age groups can be affected by CU, but the peak age is between 20 and 40 years [21]; therefore, few studies on CU in the aged population have been performed.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In our study, we found a lack of female predominance in the elderly CU group, despite a 57.9% proportion of females in the total study population. This finding is in concordance with a previous report of an almost equal sex distribution in an elderly CU group [17]. All age groups can be affected by CU, but the peak age is between 20 and 40 years [21]; therefore, few studies on CU in the aged population have been performed.…”
Section: Discussionsupporting
confidence: 92%
“…The features of elderly CU are not due to structural and physiological changes in aging skin; therefore, our results showing no significant differences between the two groups in UAS or in the prevalence of severe CU exist despite changes in dermal thickness and the number of mast cells. This similarity in UAS for both groups is in agreement with a previous report [17]. To estimate urticarial activity accurately, recent trials have used UAS 7, which averages the daily UAS over 1 week [24].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations